2022
DOI: 10.3390/jcm11164916
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism Presenting with Pulmonary Infarction: Update and Practical Review of Literature Data

Abstract: Pulmonary infarction (PI) is a possible consequence of pulmonary embolism (PE). The real incidence of PI could be underestimated considering only non-fatal PE presentation. However, following postmortem examination, the prevalence of PI is considerably higher. This evidence suggests the necessity of proper diagnostic protocol for identifying PI. Unfortunately, PI diagnosis can sometimes be challenging, due to the overlapping of symptoms with other diseases. Nowadays, the diagnosis is mainly based on radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…As the lung tissue has a dual circulation through pulmonary and bronchial vasculatures and directly absorbs oxygen through alveolar ventilation, the lung has partial resistance to ischemic damage. Recent research reported that the prevalence of PI was 16% to 31% ( 4 - 6 ). In our research, 16.58% of PE patients had PI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the lung tissue has a dual circulation through pulmonary and bronchial vasculatures and directly absorbs oxygen through alveolar ventilation, the lung has partial resistance to ischemic damage. Recent research reported that the prevalence of PI was 16% to 31% ( 4 - 6 ). In our research, 16.58% of PE patients had PI.…”
Section: Discussionmentioning
confidence: 99%
“…A lung section would suffer from a pulmonary infarction (PI) when its blood supply is cut off, causing the tissue to perish. The literature states that the prevalence of PI ranges from 16% to 31% ( 4 - 6 ).…”
Section: Introductionmentioning
confidence: 99%